Combination of Gonadal Dysgenesis and Monosomy X with a Novo Translocation (13,14) - Hanane Latrech; Houssein Madar; Ahmed Gaouzi (Case Reports in Endocrinology)
Turner syndrome is a common sex chromosome disorder characterized by complete or partial absence of an X chromosome. The spectrum of its clinical features and cytogenetics are various. We report new chromosomal formula revealed by DSD and associated with translocation (13,14). To our knowledge, this is the first case of 45X, t(13;14) de novo translocation as a variation of Turner syndrome in a patient with this clinical presentation.